The Construction of Genetic Map of Faba Bean (Viciafaba L.) Using RAPD Markers - Memen Surahman (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2001)
Fifty seven individuals of recombinant inbred lines (RlLs) of faba bean (Viciaf aba L.) descended from the cross between 34Morocco x Kristal125 have been analyzed for RAPD markers. A total of 77 markers were assayed segregating in the 57 Rl lines and grouped into 14 linkage groups, with total length of 973.2 cM Key words: Vicia faba, Recombinant in bred line, RAPDs, Linkage groups